Effects of interoceptive training on decision making, anxiety, and somatic symptoms - Sugawara, Ayako (Biopsychosoc Med, 2020)
BACKGROUND: Interoception is the perception of afferent information that arises from any point within the body. Individual differences in interoception have been associated with affective processing and decision-making processing. The somatic marker hypothesis summarizes the potential effects of interoception on decision-making processes. According to this theory, individuals with interoceptive dysfunction exhibit disadvantageous decision making. Recently, enhancement of interoceptive accuracy, an element of interoception assessed by objective decision-making tasks, has been demonstrated using biofeedback. Garfinkle et al. developed an interoceptive training task, modified from the heartbeat perception task, which enhanced interoceptive accuracy and reduced anxiety symptoms. The purpose of this study was to determine the effects of interoceptive training on decision-making processes. Based on improvements in interoceptive accuracy, we hypothesized that decision-making scores would change in a manner indicative of increased rationality. METHODS: This longitudinal interventional study was performed with interoceptive training. Before and after the intervention, interoceptive accuracy and rationality of decision-making processes were assessed using a heartbeat perception task and rational decision-making tasks, respectively. Fourteen healthy volunteers (nine women; mean age, 21.9 ± 4.5 years) participated. The analysis included data from 12 participants. To detect individual differences in the effects of interoceptive accuracy on rationality of decision making, correlation analysis was conducted on change ratios of the indices of interoceptive accuracy and rationality of decision making. RESULTS: Interoceptive training resulted in significant enhancement of interoceptive accuracy scores and significant reductions in somatic symptom and state anxiety scores. In contrast, interoceptive training did not cause significant changes in decision-making indices. There was a significant positive correlation between change ratios of indices of interoceptive accuracy and rationality of decision making. CONCLUSIONS: The results suggested a causal relation between interoception and rationality of decision making. These findings will enhance the understanding of mechanisms underlying alterations of decision-making related to psychotherapy by focusing on interoception. TRIAL REGISTRATION: Trial registration number: UMIN000037548.